Soil Stress-Strain Behavior: Measurement, Modeling and Analysis A Collection of Papers of the Geotechnical Symposium in Rome, March 16-17, 2006 - Ling, Hoe I.; Callisto, Luigi; Leshchinsky, Dov.; Koseki, Junichi; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This book is an outgrowth of the proceedings for the Geotechnical Symposium in Roma, which was held on March 16 and 17, 2006 in Rome, Italy. The Symposium was organized to celebrate the 60th birthday of Prof. Tatsuoka as well as honoring his research achievement. The publications are focused on the recent developments in the stress-strain behavior of geomaterials, with an emphasis on laboratory measurements, soil constitutive modeling and behavior of soil structures (such as reinforced soils, piles and slopes). The latest advancement in the field, such as the rate effect and dynamic behavior of both clay and sand, behavior of modified soils and soil mixtures, and soil liquefaction are addressed. A special keynote paper by Prof. Tatsuoka is included with three other keynote papers (presented by Prof. Lo Presti, Prof. Di Benedetto, and Prof. Shibuya).
Special Keynote Paper -- Keynote Papers -- Behavior of Granular Materials -- Behavior of Clays -- Soil Viscous Properties -- Modified Soils and Soil Mixtures -- Cyclic/Dynamic Soil Behavior -- Soil Liquefaction -- Constitutive Models and Numerical Analysis -- Soil Reinforcement and Earth Retaining Structures -- Piles and Buried Structures -- Slopes and Other Geotechnical Issues.
Keywords: PHYSICS; MATERIALS; BUILDING CONSTRUCTION; PHYSICS; GRANULAR MEDIA; CONTINUUM MECHANICS AND MECHANICS OF MATERIALS; BUILDING MATERIALS; STRUCTURAL FOUNDATIONS, HYDRAULIC ENGINEERING; NUMERICAL AND COMPUTATIONAL METHODS